2005
DOI: 10.1590/s0001-37652005000300004
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of the interactions of Trypanosoma cruzi and Trypanosoma rangeli within the reduviid insect host Rhodnius prolixus

Abstract: This review outlines aspects on the developmental stages of Trypanosoma cruzi and Trypanosoma rangeli in the invertebrate host, Rhodnius prolixus. Special attention is given to the interactions of these parasites with gut and hemolymph molecules and the effects of the organization of midgut epithelial cells on the parasite development. The vector insect's permissiveness to T. cruzi, which develops in the vector gut, largely depends on the host nutritional state, the parasite strain and the molecular interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 39 publications
0
35
1
2
Order By: Relevance
“…Differences in the survival of parasites have been related to an induction of lysozymes, agglutinating, prophenoloxidase, and hemocyte activity (36) (37) . For instance, the presence of T. rangeli in the hemocoel of R. prolixus activates the prophenoloxidase system, phagocytosis, hemocyte microaggregation, superoxide and nitric oxide activity, and eicosanoid biosynthesis (38) .…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the survival of parasites have been related to an induction of lysozymes, agglutinating, prophenoloxidase, and hemocyte activity (36) (37) . For instance, the presence of T. rangeli in the hemocoel of R. prolixus activates the prophenoloxidase system, phagocytosis, hemocyte microaggregation, superoxide and nitric oxide activity, and eicosanoid biosynthesis (38) .…”
Section: Discussionmentioning
confidence: 99%
“…Parasite and vector co-evolution has involved physiological or biochemical strategies, facilitating or hampering parasite development in the invertebrate host (Azambuja et al 2005). It has been observed that invertebrates have developed efficient immune mechanisms against parasite infections by producing potent antimicrobial peptides and polypeptides (Bulet et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Trypomastigotes differentiate into the epimastigote stage, to multiply asexually, before differentiating into infectious metacyclic trypomastigotes (Figure 2). Parasite viability, development and multiplication are then influenced by physiological and biochemical interactions with the vector, according to its life stage and location inside the vector (see Azambuja et al, 2005b;Garcia et al, 2007Garcia et al, , 2009.…”
Section: Triatomine-trypanosoma Interactionsmentioning
confidence: 99%